Dynamic measurement of thin liquid film parameters using high-speed ellipsometry - Yupapin, P. V.P.; Chitaree, R.; Palmer, A. W.; Grattan, K. T.V.; Weir, K. (My University, 1998)
The feasibility of the measurement of dynamic, thin liquid film properties using an ellipsometer-based fibre-optic modulation technique is presented. The essence of this technique is that a dynamic measurement of film parameters such as refractive index and Fresnel reflection coefficients may be simultaneously and automatically made, from which the instantaneous changes of liquid film thickness may be characterized. Such a scheme is discussed where a measurement rate of 25 Hz has been used to illustrate the value of the system in the monitoring of spreading liquid films. © 1998 Elsevier Science S.A.
Keywords: Dynamic measurements; High-speed ellipsometry; Thin liquid films